Bioelectromagnetic fields as signaling currents of life - Haiying Wang; Weijin Zou; Yi Cao (Radiation Medicine and Protection)
Bioelectromagnetic signaling, a fundamental aspect of biological systems, has gained increasing attention in recent years. This review synthesizes current knowledge and recent advancements in bioelectromagnetic research, covering principles, evidence, and emerging applications. We discuss the generation, reception, and roles of bioelectromagnetic fields in living organisms, focusing on intercellular and organism-level communication. The review also examines therapeutic applications, and technological innovations arising from our understanding of bioelectromagnetic phenomena. Finally, we outline future research directions that promise to deepen our comprehension of life's electromagnetic dimensions and potentially revolutionize medicine and technology.